Better Schools, Less Crime? * - Deming, David J. (Quarterly Journal of Economics, 2011)
I estimate the impact of attending a first-choice middle or high school on adult crime, using data from public school choice lotteries in Charlotte-Mecklenburg school district (CMS). Seven years after random assignment, lottery winners had been arrested for fewer serious crimes and had spent fewer days incarcerated. The gain in school quality as measured by peer and teacher inputs was equivalent to moving from one of the lowest-ranked schools to one at the district average. The reduction in crime comes largely from years after enrollment in the preferred school is complete. The impacts are concentrated among high-risk youth, who commit about 50 % less crime across several different outcome measures and scalings ofcrimebyseverity. I findsuggestiveevidencethat school qualityexplains more of the impact in high school, whereas peer effects are more important in middle school. JEL Codes: I20, I21. I.